INTER-GENDER KOMUNIKASI DALAM CYBERSPACE: APAKAH ICT DAPAT MENJADI JEMBATAN BAGI PEREMPUAN DAN LAKI-LAKI DALAM BERKOMUNIKASI? - Safitri, Reza (Jurnal Interaktif, 2010)
The emerging of information and communication technology (ICT) has changed society significantly, in term of the way they communicate. This new technology, particularly internet, enables someone to connect with anyone easily --in any parts of the world-- as geographic boundaries have now becoming âborderlessâ and the space becoming more ânarrowâ, just like a global village, as predicted by McLuhan. ICT is like a superhighway that enables information exchange activities running so quickly. This situation may lead to the alternation of social communication and interaction patterns in general. It is imperative to know whether the use of internet will change the nature of face-to-face communication into more artificial way. More specific question is that if the online system will alter the way women and men in making communication in the cyberspace. Generally, women communicate to pursue human communication, but men do the same thing for other reason, namely social status, reflecting the patriarchal culture. The question is that such âinter-genderâ communication will also present in the cyberspace, due to the absence of physical entity? Is the ICT able to cope with communication problems between women and men, as what usually happen in the real world? This paper, as part of a research project, will show the inter-gender communication through cyberspace. The dynamic of communication patterns between women and men in mailing list will be assessed. Evaluation will be given to the possibility of the interaction pattern changes due to the present of ICT.Keywords: ICT, cyberspace, communication, gender